2020
DOI: 10.3390/su12062521
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Quality Monitoring of Open-Graded Aggregates by Light Weight Deflectometer and Soil Stiffness Gauge

Abstract: Open-graded aggregates (OGAs) are free-draining materials often used as the base layer of permeable pavements to allow the infiltration or drainage of stormwater. Despite their widespread use, the compaction quality of OGA base layers has not been specified properly. The currently used density-based compaction quality control (QC) has limitations; obtaining the field density and maximum dry density of OGAs by typical methods is challenging, due to their unique properties. To overcome these limitations, modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Additionally, the results of the measured force and the derived deflection show very good agreement between different trial measurements, leading to negligible differences in the estimated elastic modulus. The results of the newly developed LWD were systematically compared with those of Choi et al [ 43 ], who had extensively used the ZFG 3000 (Zorn Instruments, Stendal, Germany [ 40 ]) and Soil Stiffness Gauge (SSG, Humboldt, IL, USA [ 44 ]) to determine the modulus of elasticity of D40 and D25 materials. Their measurements showed that for the D40 material with a dry density from 15.39 to 16.25 kN/m³, the ZFG 3000 gave values between 25.50 and 42.10, while the SSG measurements ranged from 38.20 to 49.18 kN/m³.…”
Section: Materials and Testing Resultsmentioning
confidence: 99%
“…Additionally, the results of the measured force and the derived deflection show very good agreement between different trial measurements, leading to negligible differences in the estimated elastic modulus. The results of the newly developed LWD were systematically compared with those of Choi et al [ 43 ], who had extensively used the ZFG 3000 (Zorn Instruments, Stendal, Germany [ 40 ]) and Soil Stiffness Gauge (SSG, Humboldt, IL, USA [ 44 ]) to determine the modulus of elasticity of D40 and D25 materials. Their measurements showed that for the D40 material with a dry density from 15.39 to 16.25 kN/m³, the ZFG 3000 gave values between 25.50 and 42.10, while the SSG measurements ranged from 38.20 to 49.18 kN/m³.…”
Section: Materials and Testing Resultsmentioning
confidence: 99%
“…There are two common types of pavement assessment, specifically structural evaluation and functional evaluation [8]. Road pavement performance assessment is a method that includes a review of the performance of the road pavement during the road's service life [9]; this is essential for maximizing the function and quality of the road pavement itself [10]. Evaluation operations are directly tied to a pavement's repair and maintenance programme, assessing the road's geometric and structural qualities [11].…”
Section: Performance Evaluation Of Flexible Pavementmentioning
confidence: 99%
“…This moisture content is referred to as the optimum moisture content (OMC), and at this water content, the sample would record its maximum dry density (MDD). The MDD provides an overall indication of the quality of a mixture where a greater MDD is commonly associated with samples containing higher quality aggregates, thus undergoing a higher degree of compaction, while lower values indicate possible porosity of aggregates [80,81].…”
Section: Compaction Test (Standard/modified)mentioning
confidence: 99%